'We're just like Gok, but in reverse': Ana Girls – empowerment and resistance in digital communities. Issue 3 (2nd July 2016) - Crowe, Nic; Watts, Mike
Abstract : 'Pro-Ana' Internet sites can foster or celebrate anorexia and bulimia nervosa in young women. Clinical discourse portrays anorexia as a problematic and deviant 'condition', while Pro-Ana/-Mia spaces offer an arena that appeals to control over how bodies are represented. We draw on data from a seven-year ethnographic study of young people's online worlds, from forums, postings on Pro-Ana sites and online interviews with Pro-Ana users, to illustrate and illuminate young women's perspectives and the extent to which this transgressive movement strives for voice. We argue that 'being' Pro-Ana offers 'practitioners' liberation from cultural critiques of the body. The websites suggest that famously thin women, whose 'beauty' has already been culturally validated, have overcome similar problems to Pro-Ana readers, and offer a re-formulation of cultural identities to provide legitimate (and validated) means to reach this 'perfection'. In this respect, they represent important sites of agency and resistance.